Keanekaragaman Tanaman Bermanfaat Obat oleh Masyarakat Desa Mekarjaya, Bayung Lencir. - Vria Andesmora, Evan; Aprianto, Riko; Novallyan, Devie (Jurnal Hutan dan Masyarakat, 2024)
Society's use of medicinal plants has been an essential part of human history since ancient times. This is triggered by the human need to treat various diseases and cure various health conditions. The research was conducted in March 2022. Data was collected using the exploration method, and information on plant types was collected in the form of regional names, scientific names, family names, Indonesian names, and growing environments. After creating tables and graphs, descriptive analysis was carried out on the data. The findings revealed that the people of Mekarjaya Village have used 26 different types of medicinal plants, with leaves as the most commonly used plant organ, namely 12 plants, rhizomes, and fruit, each six plants, three plants for stems, two plants for roots and one plant for flower. This type of plant is obtained or cultivated in home gardens and is usually used for drinking. The habitat of medicinal plants is mainly in the yard. Additionally, medicinal plants are used by consuming or rubbing them on the body.